CZTS solar cells and the possibility of increasing VOC using evaporated Al2O3 at the CZTS/CdS interface. (1st March 2020) - Ojeda-Durán, E.; Monfil-Leyva, K.; Andrade-Arvizu, J.; Becerril-Romero, I.; Sánchez, Y.; Fonoll-Rubio, R.; Guc, M.; Jehl, Z.; Luna-López, J.A.; Muñoz-Zurita, A.L.; Hernández-de la Luz, J.A.D.; Izquierdo-Roca, V.; et al.
Highlights: CZTS solar cells with and without Al2 O3 very thin layer was used on the CZTS/CdS interface. Al2 O3 thin layer was deposited by thermal evaporation. An increase in Voc with the use of thermally evaporated Al2 O3 was demonstrated. A band diagram of the structure CZTS/Al2 O3 /CdS/ZnO/ITO showed a difference on energy in VBO. Abstract: We report the effect of an ultra-thin Al2 O3 layer (down to 3 nm) as interface passivation strategy for the improvement of the performance of Cu2 ZnSnS4 /CdS based solar cells. After an initial optimization, the Al2 O3 deposited by thermal evaporation is proved to improve the properties of the p-n junction. The fabricated devices showed an increment in Voc depending on the composition of the absorber, and an improvement in fill factor (FF) apparently related to the insulation of possible shunt-paths. Also, the impact on other optoelectronic parameters is discussed.